A new distance learning national framework for social work continuing education: critical reflections on the first phases of implementation - Tracey Maegusuku-Hewett (Social Work Education, 2018)
This article utilises a range of secondary research methodologies in an exploration of the challenges and opportunities that have arisen from the establishment and first years of delivery of a new single and predominantly distant learning national post-qualifying framework. The CPEL framework is directly commissioned by the professional regulator Social Care Wales (SCW, formerly the Care Council for Wales (CCW)), provided by an alliance of four universities (Bangor, Cardiff, Glyndwr and Swansea) and actively involves employers, practitioners and service users in their development. Critical reflections on the early implementation of the Experienced, Senior and Consultant Programmes that contribute to the CPEL framework will help understand the key characteristics, challenges and opportunities post qualifying education for social workers can bring. The paper commences with an analysis of the moves to design a national post-qualification framework that is more accessible, flexible and responsive than the previous patchwork quilt set-up, including an examination of the increased role of distance learning and the teaching methodologies that support it. It then critically summarises the specific context and developments of the CPEL framework. This is followed by substantive analyses of the key messages. These messages are of the value of; provider collaboration, quality of e learning experience, employer commitment and student perceived competence/satisfaction.